Revisiting Bodies in Interior Design Practice - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2024)
Addressing human bodies is inevitable in interior inquiries and practices. Integrating knowledge about human bodies into design practice can extend beyond the idea of bodies as merely static entities with fixed dimensions. The idea of bodies as the basis for spatial design practice views the human body as a living entity that dwells, occupies, moves, and engages in space. Knowledge about bodies as the basis of practice also needs to view bodies' presence as sociocultural entities. The emergence of the virtual environment provides another context with a shifting materiality of bodies and interior spaces. This issue of Interiority acknowledges the breadth of knowledge about bodies in spatial design disciplines. The articles demonstrate various ideas that reflect some challenges surrounding the integration of knowledge about bodies into design practice.